PENGGUNAAN PENDEKATAN SAVI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR APRESIASI MUSIK NUSANTARA PADA SISWA KELAS VIII C SMP NEGERI 2 SUGIO KABUPATEN LAMONGAN - Umi Kulsum (MEDIA DIDAKTIKA, 2022)
The purpose of this study was to describe (1) whether the use of the SAVI approach can improve learning activities for archipelago music appreciation and (2) whether the use of the SAVI approach can improve learning outcomes for archipelago music appreciation in class VIII C students of SMP Negeri 2 Sugio. This research is a qualitative descriptive research, namely research that describes the steps of learning and the results of the learning process with the SAVI approach. The results showed that the results of activity observations showed that in cycle 1 the attention aspect 22 children scored high, interaction 21 children scored high, assignment 22 children scored high and cooperation 21 children scored high. Based on the results of the research, the authors concluded that the SAVI approach can increase the activity and learning outcomes of appreciation of Indonesian music for students and the authors suggest that this SAVI approach can be continuously applied by teachers in the learning process at school so that student activities and learning outcomes can be even better.